Modeling of H₂S adsorption with hydrogel biochar - Rozi, Mohd Danish (2019)
The purpose of this study is to model the adsorption of sour gas on hydrogel biochar bio adsorbent. Conventional activated carbon is expensive and has environmental concerns since it is not bio-degradable which leads to the attention in finding a cheaper, eco-friendly material from readily available renewable sources and hydrogel is seen as a viable alternative. Adsorption tests have been carried out in a fixed-bed column, at different flowrate of 200 L/h, 100 L/h and 50 L/h and at varying bed heights in order to investigate the kinetic parameters. It was established that the adsorbent has a good H₂S adsorption capacity, owing to its surface area and composition. H₂S adsorption rate increases with lower inlet flowrate while higher bed height increases the adsorption capacity. The experimental data was fitted with pseudo-first order and pseudo-second order and it is found the first order best describes the adsorption process at sufficiently high inlet flowrate.